(3GdSajfI GdLGeYI dCfhGY GdYdhes - (3GdMGce CHj SYO GdMSf Hf cQGeI GdLTej GdHjgbj GdHQhbj,J (B494 (3g` s ((3eOjfI UYOI s)
(3ChdgG (B:s
(3HGH LedI ef TQa QShd Gddg Shi eG PcQ ai GdHGH GdPi bHd gPG eeG fWb Hg GdbQBf bhdg JYGdi (B( (3NGJe GdfHjjf (B) s
(3BNQgG (B:s
(3Mci CHh YHO Gddg Cfg bGd CZajJ djdI ef GddjGdi ai GdeTgO HWhS aQCjJ edcjf fRdG ef GdSeGA hcJHG Ydi LOGQ GdeSLO gPjf GdHjJjf hGJab GdaQGZ ef fSGNJg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI eUMMIs
(3Ydi WQJgG hZGTjJgG JedcGJ heWGdYGJ s
(3cJHJ GdahGJM hGdYfGhjf HGdSejc s
(3bQf GdfSN (B:s
Keywords: (3GdJGQjNs